2021
DOI: 10.1186/s12961-021-00721-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to conducting economic evaluation studies of Gulf Cooperation Council (GCC) countries: a survey of researchers

Abstract: Background The number of published economic evaluations of Gulf Cooperation Council (GCC) countries is notably scarce. Limited local evidence could have a major impact on the implementation of economic evaluation recommendations in the decision-making process in GCC countries. Little is known about the factors affecting researchers who seek to conduct economic evaluations. Therefore, we aimed to assess researcher barriers and facilitators in conducting such studies of GCC countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Furthermore, barriers to conducting economic evaluations still exist in this region. These barriers have been discussed elsewhere in previous studies [ 6 , 18 , 19 , 84 86 ].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, barriers to conducting economic evaluations still exist in this region. These barriers have been discussed elsewhere in previous studies [ 6 , 18 , 19 , 84 86 ].…”
Section: Discussionmentioning
confidence: 92%
“…Arrangement of such workshops and seminars on local and national levels greatly helps boost knowledge of pharmacoeconomics among students and researchers. It brings about new ideas and ways to bring innovation to the healthcare system by implementing pharmacoeconomic tools and making full use of financial resources and budget management by creating a balance between drug costs and results [42].…”
Section: Promotion Of Pharmacoeconomic Group Discussion Among Researc...mentioning
confidence: 99%
“…Almazrou et al reported that researchers face difficulty using pharmacoeconomic tools due to a lack of expertise on evaluation outcomes such as QALYs. Furthermore, there is no national governing body solely dedicated to implementing pharmacoeconomics at the local and national levels [42].…”
Section: Discussion Of Pharmacoeconomic Studies With Middle Eastern C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing interest in the role of economic evaluation in the decision-making process in Arab countries, the published literature is limited in quality and quantity [7,8]. The availability of cost and effectiveness data has been reported as the main barrier to conducting economic evaluation by researchers in the region [9].…”
Section: Introductionmentioning
confidence: 99%